DYNAMICS OF EXPORT PERFORMANCE IN SMES AND THE INFLUCENCE OF MANAGERIAL FACTORS - Bantu, Daniel Niranjan Kumar (My University, 2012)
Export performance is one of the most widely researched topics. Despite extensive research; it has remained one of the least understood areas of international marketing. The research aims to examine the export performance and its dimensions and to understand the influence of managerial factors on export performance. The theoretical work used in this study is mostly based on the export management. Literature on export performance and three dimensions are discussed to provide a broad understanding on outcomes of a firm’s activities in export markets. Managerial factors are selected in order to understand the influences on export performance. Empirical part of the thesis analyzed the finding of the study regarding the association between three dimensions namely effectiveness, efficiency and adapativeness and the link between managerial influences on exporting firm. This study adopted a qualitative approach based on a multi case study engaging semi structured interviews to study the export performance of Finnish exporting companies. The findings of the case study shows multi-dimensional approach will help the managers to understand its performance with multiple levels there by allowing greater control in decisions making process. The managerial factors selected in this study consist of international outlook, commitment, perceived export stimuli and barriers, language and innovation. Findings related to managerial factors supports that in practice exporting companies with few resources can successfully achieve and maintain better results with international orientated managers.
Keywords: Export Performance; Performance Dimensions; Managerial Factors.; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|